2019
DOI: 10.1002/ecm.1382
|View full text |Cite
|
Sign up to set email alerts
|

Plant responses to nutrient addition experiments conducted in tropical forests

Abstract: I present a meta‐analysis of plant responses to 48 nutrient addition experiments conducted with native species in naturally growing tropical forests, exclusive of mangrove forests. The added nutrients include nitrogen (N) in 36 experiments, phosphorus (P) in 33 experiments, calcium and potassium in one experiment each, and various mixtures of essential nutrients in the remaining experiments. I evaluate the hypotheses that nutrients limit tropical forest plants, nutrient limitation is stronger in successional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
111
2
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(126 citation statements)
references
References 80 publications
10
111
2
3
Order By: Relevance
“…The amount of nutrients added in this experiment therefore correspond to twice the annual N input and 35 times the annual P input from leaf litter decomposition (Bonal et al, 2008;Hättenschwiler et al, 2008;Barantal et al, 2012). Our nutrient addition is similar to the amount of nutrients applied in other fertilization experiments in tropical forests (Wright et al, 2018;Wright, 2019).…”
Section: Fertilization Treatmentssupporting
confidence: 60%
See 1 more Smart Citation
“…The amount of nutrients added in this experiment therefore correspond to twice the annual N input and 35 times the annual P input from leaf litter decomposition (Bonal et al, 2008;Hättenschwiler et al, 2008;Barantal et al, 2012). Our nutrient addition is similar to the amount of nutrients applied in other fertilization experiments in tropical forests (Wright et al, 2018;Wright, 2019).…”
Section: Fertilization Treatmentssupporting
confidence: 60%
“…Apart from drought, changes in nutrient availability also impact soil gas fluxes in tropical forests. It is generally acknowledged that P rather than N is limiting in lowland tropical forests (Martinelli et al, 1999;Camenzind et al, 2018;Wright et al, 2018;Wright, 2019), and therefore we might expect stronger effects of P addition rather than N addition. In agreement with this, in several tropical forests around the world it has been shown that P addition tends to result in a strong increase in microbial biomass (Cleveland et al, 2002;Kaspari et al, 2008;Liu et al, 2013;Fanin et al, 2015).…”
Section: Introductionmentioning
confidence: 84%
“…We found a strong relationship with soil N only (r 2 = 0.65; p < 0.1) ( Fig. 4a), suggesting that canopy greenness in tropical forests in Panama is predominantly driven by soil N, but not by other nutrients 23,76 . This could reflect the strong association between foliar N and chlorophyll content, with plants taking up additional N even in N-rich soils ("luxury consumption").…”
Section: Resultsmentioning
confidence: 87%
“…Although N can limit growth in regenerating forests in eastern Amazonia (Davidson et al, 2004) and there is increasing evidence of nutrient colimitation in the tropics (Wright, 2019), the strongly weathered nature of the tropical landscape means that P is more likely to limit growth (Vitousek, 2004). Indeed, recent evidence suggests that such limitation occurs broadly at the species level (Turner et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the productivity of lowland tropical forests is generally thought to be limited by soil phosphorus (P), rather than by N (Cleveland et al, ; Turner, Brenes‐Arguedas, & Condit, ; Vitousek, ). Although N can limit growth in regenerating forests in eastern Amazonia (Davidson et al, ) and there is increasing evidence of nutrient colimitation in the tropics (Wright, ), the strongly weathered nature of the tropical landscape means that P is more likely to limit growth (Vitousek, ). Indeed, recent evidence suggests that such limitation occurs broadly at the species level (Turner et al, ).…”
Section: Introductionmentioning
confidence: 99%